Enhanced electron transfer mediator based on biochar from microalgal sludge for application to bioelectrochemical systems. (September 2018) - Lee, Ja Hyun; Kim, Dong Sup; Yang, Ji Hyun; Chun, Youngsang; Yoo, Hah Young; Han, Sung Ok; Lee, Jinyoung; Park, Chulhwan; Kim, Seung Wook
Graphical abstract: Highlights: The microalgal sludge (MS) was activated for conversion to biochar (MSB). Co and chitosan was synthesized on the surface of MSB as mediator (MSB/Co/chitosan). MSB/Co/chitosan mediator was successfully utilized in the EFC system and biosensor. Abstract: This study is focused on the utilization of waste microalgal sludge (MS) from microalgal extraction and its potential as an electrode material. The MS was activated under N2 at high temperature for conversion to biochar (MSB). In addition, cobalt (Co; metal hydroxide) and chitosan were used as a mediator for electron transfer by immobilization on MSB (MSB/Co/chitosan). Through analysis of the surface and components of the MSB/Co/chitosan, it was shown that Co and chitosan were properly synthesized with MSB. The enzymatic fuel cell (EFC) system successfully obtained a power density of 3.1 mW cm −2 and a current density of 9.7 mA cm −2 . In addition, the glucose biosensors applied with the developed electron transfer mediator showed a sensitivity of 0.488 mA mM −1  cm −2 .